2001
DOI: 10.1074/jbc.m100556200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of p85 Relieves Its Inhibitory Activity on Phosphatidylinositol 3-Kinase

Abstract: Under resting conditions, the p85 regulatory subunit of phosphatidylinositol 3-kinase (PI3K) serves to both stabilize and inactivate the p110 catalytic subunit. The inhibitory activity of p85 is relieved by occupancy of the NH 2 -terminal SH2 domain of p85 by phosphorylated tyrosine. Src family kinases phosphorylate tyrosine 688 in p85, a process that we have shown to be reversed by the activity of the p85-associated SH2 domain-containing phosphatase SHP1. We demonstrate that phosphorylation of the downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
200
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(213 citation statements)
references
References 23 publications
9
200
1
Order By: Relevance
“…However, only class I PI3K is able to phosphorylate PI (4,5) phosphate to PI (3,4,5)-phosphate (29). There are four members of class I PI3K in mammalian cells: ␣-, ␤-, ␥-, and ␦-isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only class I PI3K is able to phosphorylate PI (4,5) phosphate to PI (3,4,5)-phosphate (29). There are four members of class I PI3K in mammalian cells: ␣-, ␤-, ␥-, and ␦-isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PI3K activity is regulated by PTK through tyrosine phosphorylation (4,15). The catalytic activity of p110␣ is suppressed by association with an 85-kDa regulatory subunit (p85␣).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4c). Although the Src family kinases such as Lyn may phosphorylate tyrosine residues on p85α, the exact function of p85α tyrosine phosphorylation remains unclear 21,22 . In this cell-free system, p85α tyrosine phosphorylation appeared to be necessary for RGS13 complexation as no RGS13 binding to p85α was observed in the absence of p85α phosphorylation (Supplementary Figure 5 online).…”
Section: Rgs13 Interacts With Pi(3) Kinasementioning
confidence: 99%
“…The activated PI3-K converts the lipid PI (4, 5) P2 to PI (3, 4, 5) P3 by phosphorylating the substrate at the C3-position of the inositol ring. The serine/threonine kinases PDK1 (3 -phosphoinositide dependent kinase 1) and Akt preferentially bind to PIP3 via their PH domains, which lead to Akt activation depending on its phosphorylation at Ser473 and Thr308 sites by PDK1 (Cuevas et al, 2001;Fruman et al, 1998). Phosphatase and tensin homolog (PTEN), also known as mutated in multiple advanced cancers (MMAC1) converts PIP3 to PIP2 and acts as a negative regulator of the PI3-K pathway (Stambolic et al, 1998).…”
Section: Pi3-kinase/akt Pathway Controls Cell Survival Cell Cycle Anmentioning
confidence: 99%